RELEVANSI PENDIDIKAN KRITIS DALAM MENGHADAPI BERBAGAI TANTANGAN PENDIDIKAN KONTEMPORER [THE RELEVANCE OF CRITICAL EDUCATION IN FACING VARIOUS CHALLENGES OF CONTEMPORARY EDUCATION] - Rahmat, Hayatul Khairul; Subaidah, Siti; Darojah, Indah; Mulyana, Asep (Perkumpulan Ahli Bimbingan Konseling Islam Indonesia, 2025)
This article explores the urgency and relevance of critical education in addressing various contemporary educational challenges, such as the commercialization of education, inequality in access, decontextualized curricula, digital transformation, inclusivity, and gender issues. Using a library research approach, the authors examine the concept of critical education grounded in the thoughts of Paulo Freire and other figures like Ki Hadjar Dewantara, while highlighting how critical education fosters reflective thinking, social awareness, and active student participation. The article also presents best practices from Indonesia, such as community-based education, local curricula, and alternative schools, which are seen as effective in embodying the principles of critical pedagogy in real-world contexts. Thus, critical education is viewed as a strategic solution to equip the younger generation in navigating the complexities of global change with wisdom and responsibility.